Water Extract of Potentilla discolor Bunge Improves Hepatic Glucose Homeostasis by Regulating Gluconeogenesis and Glycogen Synthesis in High-Fat Diet and Streptozotocin-Induced Type 2 Diabetic Mice - Li, Tiange; Chang, Rui; Zhang, Huijuan; Du, Min; Mao, Xueying (Frontiers in Nutrition, 2020)
Potentilla discolor Bunge, as a traditional Chinese medicine, exhibits many phytochemical activities. The aim of the present study was to investigate the effects of Potentilla discolor Bunge water extract (PDBW) and its underlying mechanisms on gluconeogenesis and glycogen synthesis in high-fat diet/streptozotocin (HFD/STZ)-induced type 2 diabetic mice. LC-MS/MS analyses of PDBW identified 6 major compounds including apigenin-7-O-β-D-glucoside, epicatechin, quercetin 3-O-β-D-glucuronide, kaempferol-3-O-β-D-glucopyranoside, scutellarin, and quercitrin. In the study, a mouse model of type 2 diabetes was induced by 4-week HFD combined with STZ (40 mg/kg body weight) for 5 days. After oral administration of PDBW at 400 mg/kg body weight daily for 8 weeks, the mice with type 2 diabetes showed significant decrease in the levels of fasting blood glucose and glycated hemoglobin A1c (HbA1c), and increase in the insulin level. PDBW improved the glucose tolerance, insulin sensitivity and lipid profiles. Furthermore, PDBW inhibited the mRNA levels of key gluconeogenic enzymes [phosphoenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphatase (G6Pase)] in liver. PDBW also promoted glycogen synthesis by raising the liver glycogen content, decreasing the phosphorylation of glycogen synthase (GS) and increasing the phosphorylation of glycogen synthase kinase3β (GSK3β). Besides, PDBW induced the activation of protein kinase B (Akt) and AMP-activated protein kinase (AMPK), which might explain changes in the phosphorylation of above enzymes. In summary, PDBW supplementation ameliorates metabolic disorders in a HFD/STZ diabetic mouse model, suggesting the potential application of PDBW in prevention and amelioration of type 2 diabetes.